Integration of Ethno-Counseling in Preserving Local Wisdom Values in Batak Mandailing Traditional Wedding Ceremonies - Ghoffar, Helmi; Ahman, Ahman; Ilfiandra, Ilfiandra (Kuras Institute, 2024)
This research aims to explore the application of ethno-counseling in the context of Mandailing Batak marriages, focusing on integrating Dalihan Natolu cultural values ​​in the counseling process. The research method uses a phenomenological and field research approach involving direct observation, interviews, and documentation with1 prospective bride and groom couples who follow this tradition as respondents. This research design is qualitative-based with triangulation data analysis to ensure the validity of the findings. The research results show that ethno-counseling, which integrates values ​​such as